21st century geography a reference handbook - Stoltman, Joseph P. (21st century reference series., 2012)
Using 80 mini-chapters, this title highlights the most important topics, issues, questions and debates any student obtaining a degree in this field ought to have mastered for effectiveness in the 21st century.